2005
DOI: 10.1097/01.don.0000148145.81366.a5
|View full text |Cite
|
Sign up to set email alerts
|

Periapical Tissue Responses and Cementum Regeneration with Amalgam, SuperEBA, and MTA as Root-End Filling Materials

Abstract: The purpose of this study was to compare the periapical tissue responses and cementum regeneration in response to three widely used root-end filling materials, amalgam, SuperEBA, and Mineral Trioxide Aggregate (MTA). These materials were placed using modern microsurgical techniques on endodontically treated dog premolars and molars. After 5 months, the cell and tissue reactions of surface-stained un-decalcified ground sections were evaluated by light microscopy and statistically analyzed. The major difference … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
139
0
13

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 172 publications
(157 citation statements)
references
References 26 publications
5
139
0
13
Order By: Relevance
“…The tissue facing reinforced zinc oxide eugenol cement contained a few inflammatory cells and this result was in agreement with those of Baek et al 30) . However, the degree of inflammation was extremely mild and the bone resorption was not significantly different among the SB, EBA, and MTA groups.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The tissue facing reinforced zinc oxide eugenol cement contained a few inflammatory cells and this result was in agreement with those of Baek et al 30) . However, the degree of inflammation was extremely mild and the bone resorption was not significantly different among the SB, EBA, and MTA groups.…”
Section: Discussionsupporting
confidence: 92%
“…Cementum-like tissue formation on the resected dentinal surface and mineral trioxide aggregate has been reported 30,[33][34][35][36] . In the present study, cementum-like tissue deposition was observed on the resected dentinal 6,9,10) , although a gradual increase in leakage over long periods has also been reported 12) .…”
Section: Discussionmentioning
confidence: 99%
“…It has been shown that MTA yields better results because it produces less leakage than other materials used in root-end filling (10). According to our results, MTA can be a more effective sealing retrofilling material than amalgam, independently of the root end preparation or instrument used for this preparation.…”
Section: Discussionsupporting
confidence: 57%
“…The goals of apicoectomy are to remove a persistent periapical lesion, prevent its recurrence, and promote tissue repair (9,10). Promoting a secure seal is one of the main purposes of retrofilling and it can be assessed using an in vitro leakage test (2,3,11).…”
Section: Discussionmentioning
confidence: 99%
“…It can also promote the regeneration of alveolar bone 39 and cementum 40, 41. This case made use of MTA to seal the root canal orifice of the additional root to prevent infections and blood flow to the main root canal during the periodontal surgery.…”
Section: Discussionmentioning
confidence: 99%